THU0207 HELPER AND CYTOTOXIC FOLLICULAR T-CELLS IN SJÖGREN'S SYNDROME. (June 2019) - Barcelos, Filipe; Martins, Catarina; Monteiro, Ricardo; Geraldes, Carlos; Papoila, Ana Luísa; Cardigos, Joana; Madeira, Nathalie; Alves, Nuno; Vaz-Patto, José; Branco, Jaime; Borrego, Luís Miguel
Abstract : Background: Follicular T-cells, characterized by the expression of CXCR5, secrete interleukin 21 (IL-21) and help B-cell differentiation in lymphoid follicles. They are also found in circulation and may play a key role in Sjögren's syndrome's (pSS) chronic autoimmune epithelitis. Objectives: To characterize circulating follicular helper (Tfh) and cytotoxic (Tfc) T-cells in peripheral blood (PB) from pSS patients, Rheumatoid Arthritis (RA) patients and healthy controls (HC), and to investigate how they correlate with B-cell subsets. We also aimed to explore associations between the Tfh and Tfc cells and clinical and laboratory features of pSS. Methods: PB from 57 pSS patients, 20 RA patients and 24 HC was analysed by flow cytometry to characterize T and B-cell subsets, with CXCR5 defining Tfh and Tfc within CD4 and CD8 T cells, respectively. A stimulation assay was used to assess the production of IL-21 by CD4 + and CD8 + T-cells. Results: Compared to HC, pSS and RA patients presented significantly lower lymphocyte absolute counts (1615 and 1935 cells/μL respectively, compared to 2228 cells/μL in HC, p<0.001 for HC vs pSS, p=0.018 for HC vs RA), and percentages (29.9% in pSS, 24.0% in RA, and 35.4% in HC, p=0.022 for HC vs pSS, and p<0.001 for HC vs RA). B-cell and T-cell absolute counts were also lower in both groups of patients compared to HC (in HC vs pSS, p=0.011 for B-cells and p<0.001 for T-cells; in HC vs RA, p<0.001 for B-cells and p=0.018 for T-cells). B-cells absolute counts and percentages in pSS were higher than in RA (177 vs 132 cells/μL, p=0.013; 9.7 vs 6.4%, p<0.001). There were no differences in CD8 T-cells percentages between groups, but pSS had lower CD4 T-cell percentages compared to HC (p= 0.004). pSS patients presented lower absolute counts of CXCR5+ Tfh compared to RA (134 vs 181 cells/μL, p=0.038) and HC (134 vs 241 cells/μL, p<0.001). No differences were found in Tfh percentages. RA patients had lower percentages of CXCR5+ Tfc compared to pSS (2.1 vs 2.6%, p=0.113) and HC (2.1 vs 3.0%, p=0.046). pSS patients exhibited higher percentages of IL21 + CD4 and IL21 + CD8 T cells (IL21 + CD4 T cells: 12.4% in pSS vs 9.0% in RA, p=0.046; vs 9.7% in HC, p=0.028; IL21 + CD8 T cells: 4.1% in pSS vs 2.3% in RA, p=0.001; vs 2.8% in HC, p=0.030). In pSS patients, CXCR5+ Tfh correlated positively with the percentages of plasmablasts (r=0.262 for CD24 - CD38 ++ cells, and r=0.282 for IgM -/+ CD38 ++ cells). IL21 + CD8 T cells correlated positively with the Naïve/Memory B cells ratio (r=0.323; p=0.014) and negatively with Bm1 memory B cells (r=-0.370; p=0.005). IL21+CD4 T cells behaved similarly, though without statistical significance. Anti-SSA-positive patients (n=38) presented higher CD4 + IL21 + (13.3 vs 8.5%, p=0.025) and CD8 + IL21 + cells percentages (4.4 vs 4.0%, p=0.198) than SSA-negative patients (n=19). Although there were no differences between pSS patients with active (n=27) and inactive disease (n=30), a tendency for positive correlations was found between IL-21 + CD4 and IL21 + CD8 T-cells and the ESSDAI score (r= 0.229, p=0.086 for CD4, r= 0.223, p=0.096 for CD8). Moreover, ESSDAI correlated positively with the Tfh1/Tfh17 ratio. Conclusion: pSS patients present a profile of circulating Tfh and Tfc distinct from RA and HC, both phenotypically and functionally. Moreover, our data support a crucial role for these cells in B cell development, as they correlate with B cells, in pSS patients, which are known to exhibit a typical circulating B cell compartment. Both Tfc and Tfh cells can be critical for disease pathophysiology and activity, as underlined by the correlations between these cells and ESSDAI scores. Disclosure of Interests: Filipe Barcelos Consultant for: Pfizer; Ely-Lilly, Speakers bureau: Novartis, Catarina Martins: None declared, Ricardo Monteiro: None declared, Carlos Geraldes: None declared, Ana Luísa Papoila: None declared, Joana Cardigos: None declared, Nathalie Madeira: None declared, Nuno Alves: None declared, José Vaz-Patto: None declared, Jaime Branco: None declared, Luís Miguel Borrego Grant/research support from: MSD, Consultant for: MSD; Tecnifar, Paid instructor for: MSD; AstraZeneca, Speakers bureau: MSD; Tecnifar; AstraZeneca